A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages additional duties on local authorities for treatment in these cases) will be paid to joint authorities in aid of the hospital and consultant service. A similar grant will be paid to voluntary hospitals (the £10 millions referred to above). (2) Every new service, other than the hospital and consultant service, will be assisted by a 50 per cent. grant which will be paid to the authority responsible for the service. (3) When the above grants have been paid the joint authorities will meet the remainder of their expenditure by precept upon their constituent county and county borough councils. These councils will meet the precept and their expenditure on their own services by a rate charge, but the charge will be mitigated by an additional Exchequer grant amounting to 50 per cent. of the increase in the total cost of the health services in any year over the cost in a selected standard year. The grant will be adjusted to give more help to poor areas and less to rich. Cost to taxpayer and ratepayer How far the central funds will consist of, or be assisted by, sums of money set aside out of contributions under a social insurance scheme will be considered later. The Beveridge Report proposed that an annual sum of about £40 millions should be available from this source for the new health services. Of this, nearly £36 millions would be the share appropriate to England and Wales, and if this assistance is assumed the approximate proportions in which the total cost of the new service will fall on the social insurance scheme, the taxpayer and the ratepayer will be (ignoring the effect of the block grant under the Local Government Act, 1929), as follows :— Social insurance scheme .. .. £36 millions. Taxpayer........ £48 „ Ratepayer........ £48 „ £132 Finance in Scotland It is estimated on the same basis that the total cost to public funds of the scheme in Scodand will be nearly £16 millions, of which about £3½ millions will be spent by the State on the practitioner service and Health Centres, about £8 millions by the new joint boards, about £3 millions by the county and large burgh councils and about millions will be paid direct to voluntary hospitals. If it is assumed that Scotland's share of any sum set aside under a social insurance scheme will be about £4¼ millions (corresponding to the figure of nearly £36 millions for England and Wales) the total cost of the new service will fall on the social insurance scheme, the taxpayer and the ratepayer in approximately the following proportions:— Social insurance scheme .. .. £4.3 millions Taxpayer........ £6.1 „ Ratepayer........ £5.4 „ £15.8 „ 27 36/H24/41